Q. 25

# Write each of the following in the form ax + by + c = 0:

(i) x = – 2 (ii) y = 6

Answer :

(i) x = – 2

⇒ x + 2 = 0

Comparing, x + 2 = 0 with ax + by + c = 0 we get,

the coefficient of x i.e., a = 1

and the coefficient of y i.e., b = 0 since, there is no term of y

and clearly, c = 2

putting the values of a, b and c in ax + by + c = 0 we get,

x + 0×y + 2 = 0

(ii) y = 6

⇒ y – 6 = 0

Comparing, y – 6 = 0 with ax + by + c = 0 we get,

the coefficient of x i.e., a = 0 since, there is no term of x

and the coefficient of y i.e., b = 1

and clearly, c = – 6

putting the values of a, b and c in ax + by + c = 0 we get,

0×x + y – 6 = 0

Rate this question :

Write each of the following in the form ax + by + c = 0:

(i) x = – 2 (ii) y = 6

RS Aggarwal & V Aggarwal - MathematicsFind four different solutions of 2x + y = 6.

RS Aggarwal & V Aggarwal - MathematicsWrite each of the following in the form ax + by + c = 0:

(i) 3x = 5 (ii) 5y = 4

RS Aggarwal & V Aggarwal - MathematicsFor what value of k does the point (k, – 3) lies on the line 3x – y = 6?

RS Aggarwal & V Aggarwal - MathematicsFind the value of k, if x = 3, y = 1 is a solution of the equation 2x + 5y = k.

RS Aggarwal & V Aggarwal - Mathematics